Targeted and immuno-biology driven treatment strategies for triple-negative breast cancer: current knowledge and future perspectives - Fremd, Carlo; Jäger, Dirk; Schneeweiss, Andreas (Expert review of anticancer therapy, 2019)
Introduction: Accounting for about 15% of breast cancer patients, triple-negative breast cancer (TNBC) is responsible for 25% of disease related deaths, more frequent distant spread and visceral metastasis. However, improving survival in TNBC failed and primary resistance, immunological ignorance and tumor heterogeneity limit clinical activity of novel therapies. In view of recent molecular, genetic and immunologic insights, this review aims to describe the current status of immunological and targeted treatments from a hypothesis driven perspective.Areas covered: Recent preclinical studies and ongoing clinical trials for immune directed and targeted treatments of TNBC are summarized, including immune-checkpoint blockade, resistance mechanisms, inhibition of poly (ADP-ribose) polymerase (PARP), combinatorial strategies as well as preclinical, hypothesis generating studies.Expert commentary: Sustained responses have been observed with immune-checkpoint blockade and PARP inhibitors demonstrated remarkable efficacy in germline BRCA mutated TNBC. In order to generate clinical success of many other, to date ineffective, targeted and immune therapies, the integration of multidimensional, large amounts of data, will be essential and likely accelerate treatment progress of TNBC.